A new flavanone glycoside with antimicrobial and cytotoxic activities from Camellia hakodae Ninh leaves - Nguyen, Thanh Tuyen; Pham, Gia Dien; Nguyen, The Hung; Nguyen, Thi Hanh; Vu, Minh Tin; Tran, Hong Ngoc; Cao, Duc Tuan; Pham, Quang Duong; Tran, Thi Thu Thuy (Vietnam Journal of Science and Technology, 2024)
ABSTRACT – HCTN8: Camellia hakodae Ninh, belonging to the golden subgroup of Camellia (Theaceae), is a Camellia species native to Vietnam and primarily found in Tam Dao, Vinh Phuc province. This study aimed to isolate and identify the flavonoids from the leaves of Camellia hakodae Ninh. As a results, a new flavanone glycoside, named camehakonin A (1), was discovered alongside six known flavonoids including isoxanthohumol (2), naringenin (3), taxifolin (4), (-)epicatechin (5), macarangin (6), and 3,5,7,3’,4’-pentahydroxy-6-geranylflavonol (7). The chemical structures of these compounds were elucidated based on analysis of their spectroscopic data and by comparison with reported NMR spectroscopy data of known compounds. All isolated flavonoids were evaluated for their antimicrobial activity against various microorganisms, including Enterococcus faecalis, Staphylococcus aureus, Bacillus cereus, Escherichia coli, Pseudomonas aeruginosa, Salmonella enterica and Candida albicans. Compound 1 exhibited significant inhibition of the tested Gram-positive bacteria (E. faecalis, S. aureus, and B. cereus) with MIC values of 128, 64, and 256 µg/mL respectively, as well as the human-pathogenic fungus C. albicans (MIC: 16 µg/mL). Furthermore, compound 1 displayed weak cytotoxicity in vitro against two cancer cell lines (KB and Hep-G2) with IC50 values of 73.70 and 221.11 µM, respectively. Notably, compounds 1-7 were isolated from the leaves of Camellia hakodae Ninh for the first time.